1967
DOI: 10.1099/00221287-49-1-81
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant of Salmonella Possessing Straight Flagella

Abstract: SUMMARYA mutant of Salmonella typhimurium produced straight flagella in phase 2 (antigen-1,a) and normal flagella in phase I (antigen-i). The straight flagella were observed by light microscopy and electron microscopy either with or without formalin fixation. Flagellar bundles of the mutant bacteria prepared in 0.25 yo methylcellulose (w/v) and examined by dark-field microscopy were also found to be straight. It was shown by electron microscopy that the component flagella of the straight flagellar bundle were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…When it was realized that flagellar filaments rotate, the suggestion was made that a phage moves along the filament ''like a nut on a bolt'' (5). This observation was consistent with the finding that mutants with straight filaments, while nonmotile, remain fully sensitive to (6). Ravid and Eisenbach (7) found that the number of phage particles adsorbed by cells, i.e., removed from the supernatant fraction, correlated only with the fraction of the population of cells whose flagella rotated incessantly; it did not correlate with the direction of rotation.…”
supporting
confidence: 83%
“…When it was realized that flagellar filaments rotate, the suggestion was made that a phage moves along the filament ''like a nut on a bolt'' (5). This observation was consistent with the finding that mutants with straight filaments, while nonmotile, remain fully sensitive to (6). Ravid and Eisenbach (7) found that the number of phage particles adsorbed by cells, i.e., removed from the supernatant fraction, correlated only with the fraction of the population of cells whose flagella rotated incessantly; it did not correlate with the direction of rotation.…”
supporting
confidence: 83%
“…I a) than those observed on motile avirulent bacteria. Other investigators have reported that bacteria with straight flagella were non-motile (Iino & Mitani, 1967;Iino, 1969).…”
Section: A K E L M a N A N D J H R U S C H K Amentioning
confidence: 95%
“…5C and D). Salmonella mutants that produce irregular flagella were described more than 40 years ago and were shown to be impaired in their movement (22). Thus, it is very likely that the structural differences identified in the flagella of both strains affect the degree of their motility.…”
Section: Molecular Fingerprinting Of Anmentioning
confidence: 99%